Hak Waris Anak Adopsi Pasca Perceraian Orang Tua Angkat: Perspektif Hukum Islam dan Hukum Positif - Nurul Fazira Damanik; Agnes Elsonya Damanik; Meri Fernandes Sinaga; Brent Hizkia Padang; Syuratty Astuti Rahayu Manalu (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
This study is based on the urgency of examining the inheritance rights of adopted children after their adoptive parents separate, examined from the perspective of Islamic law and positive regulations applicable in Indonesia. The main objective of this study is to analyze the legal status of adopted children and their inheritance rights after the adoptive parents' divorce based on both legal frameworks. The methodology used is a literature study by gathering information from various relevant references and regulations. The findings of this study indicate that under Islamic law, adopted children are not automatically entitled to inheritance, but can receive a gift, will, or mandatory will with a maximum limit of one-third of the adoptive parents' assets. Meanwhile, under Indonesian positive law, the inheritance rights of adopted children depend on the court's decision during the adoption process, and even though the adoptive parents have divorced, the inheritance rights remain recorded in accordance with the existing court decision. These findings reflect the need for legal certainty to protect the rights of adopted children and emphasize the importance of clear regulations to avoid inheritance conflicts after divorce. This study is expected to serve as a reference for policymakers and legal practitioners in addressing issues related to the inheritance rights of adopted children.